2014
DOI: 10.2147/cia.s68801
|View full text |Cite
|
Sign up to set email alerts
|

Application of creatinine- and/or cystatin C-based glomerular filtration rate estimation equations in elderly Chinese

Abstract: BackgroundNo conventional creatinine- or cystatin C-based glomerular filtration rate (GFR) estimation equation performed consistently outstandingly in elderly Chinese in our previous studies. This research aimed to further evaluate the performance of some recently proposed estimation equations based on creatinine and cystatin C, alone or combined, in this specific population.Materials and methodsThe equations were validated in a population totaling 419 participants (median age 68 [range 60–94] years). The esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The CKD‐EPI cys‐scr was defined as a reference equation. A kappa value 0.21–0.40 is considered mild agreement, 0.41–0.60 moderate agreement, 0.61–0.80 substantial agreement, and 0.81–1.00 near perfect agreement (Ye et al., 2014). The results are shown in Supplementary material Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CKD‐EPI cys‐scr was defined as a reference equation. A kappa value 0.21–0.40 is considered mild agreement, 0.41–0.60 moderate agreement, 0.61–0.80 substantial agreement, and 0.81–1.00 near perfect agreement (Ye et al., 2014). The results are shown in Supplementary material Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Cystatin C is less influenced by muscle mass, sex, age, and diet than serum creatinine (Levey et al., 2015). However, cystatin C based equations may be biased for patients suffering from thyroid disease or diseases typically treated with steroids (Ye et al., 2014). Several studies have shown that the CKD‐EPI cys‐scr equation based on a combination of serum creatinine and cystatin C achieved an ideal accuracy in a Chinese elderly population (Liu et al., 2013; Ye et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sensitivity of this biomarker is poor in evaluating early renal impairment. Cystatin C, another biomarker that is only cleared in the kidney, which increases when renal function is slightly impaired, is relatively stable for the reason that it is impervious to age, gender, diet, medications, or inflammation [ 36 , 37 ]. However, the raw data relevant to the continuous variables were a barrier to assess the postoperative renal biomarkers by meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies compared the accuracy of various eGFR formulas in various populations and clinical conditions[ 41 - 63 ]. The great majority of these studies concluded that formulas based on serum cystatin C alone or on combined cystatin-creatinine levels are superior to other formulas[ 41 - 47 , 49 , 50 , 52 - 54 , 56 - 58 , 60 - 63 ]. One study found greater accuracy with the use of the average creatinine-based and creatinine/cystatin-based eGFR formulas[ 51 ].…”
Section: Clinical Applications Of the Various Formulas Estimating Gfrmentioning
confidence: 99%